PVT experimental and modelling study of some shale reservoir fluids from Argentina - Cismondi Duarte, Martín (2018)
Shale reservoir fluids have been receiving much attention, especially during the last decade, due to the important reserves confirmed in many places around the world and the recent production growth in the United States, Argentina, and probably other countries to follow. In some fields of the Vaca Muerta formation in Argentina, the fluids can be classified as gas condensate or near-critical in some cases, presenting retrograde condensation of up to 30% in volume. This work presents compositional and PVT data of two gas condensate fluids, together with a new methodology for assigning molecular weights and densities to the different carbon number fractions when measured values are available for the whole fluid or liquid phase and only a weight fraction is collected through chromatography for each single cut. A thermodynamic modelling study of these fluids, and also a third one classified as volatile oil, is based on both the PR (Peng and Robinson, 1976) and RKPR (Redlich Kwong Peng Robinson, apud Cismondi and Mollerup, 2005) equations of state, together with different ways of characterizing the heavy fractions. The focus is on phase envelopes, but knowing only the saturation point at the reservoir temperature, and also on retrograde behavior.